Analysis by age and death cause of place of death in Sudden deaths - Yamakawa, Masanobu; Ueshima, Hirotsugu; Kita, Yoshikuni; Okayama, Akira; Hongou, Setuya; Kakuno, Fumihiko (Journal of the Japanese Association for Cerebro-cardiovascular Disease Control, 1994)
To investigate the difference in place of death in sudden death according to age and cause of death, the death certificates of deaths from 1988 to 1991 in the jurisdictional area of the Imazu Health Center (population approximately 52, 000) were serveyed. The total number of deaths from all causes for the 4 years was 1, 799 for a crude death rate of 859 per 100, 000 per year. The number of sudden deaths within 24 hours of the occurrence of an unexpected internal disease that was the underlying cause of death (SD24) was 299, or 17 percent of total death. Among these the number of sudden deaths within one hour (SD1) was 131, or 7 percent of all deaths. The rate of SD1 occurrence for men was 72 per 100, 000 in a year, which was three times that for women (21). Heart disease accounted for 62% of the SD24 and 76% of the SD1. In-hospital SD24 for persons less than 60 years old was 81% of the total. In-hospital SD24 for persons over 80 yeass old was 35%, that at home was 61%. Since almost all sudden deaths at home caused by cardiovascular disease occurred in the aged, those causes of sudden death of the aged that occur at home may not be included in the cardiovascular disease registration system.